Evaluation of Nasal Mucociliary Transport Rate by 99mTc-Macroaggregated Albumin Rhinoscintigraphy in Woodworkers. (24th July 2011) - Dostbil, Zeki; Polat, Cahit; Uysal, İsmail Önder and Bakır, Salih and Karakuş, Askeri and Altındağ, Serdar
Abstract : Woodworkers in the furniture industry are exposed to wood dust in their workplaces. The aim of this study is to investigate the effect of occupational wood dust exposure on the nasal mucociliary transport rates (NMTRs) in woodworkers. Twenty five woodworkers and 30 healthy controls were included in this study. Wood dust concentration in workplaces was measured using the sampling device. 99m Tc-macroaggregated albumin ( 99m Tc-MAA) rhinoscintigraphy was performed, and NMTR was calculated in all cases. In statistical analysis, an independent samples t -test was used to compare NMTR of woodworkers and control subjects. We found that the mean NMTR of the woodworkers was lower than that of the healthy controls. However, there was not a statistically significant difference between them (P = 0.066 ). In conclusion, our findings suggested that wood dust exposure may not impair nasal mucociliary transport rate in woodworkers employed in joinery workshops.